2019
DOI: 10.1038/s41419-019-1920-7
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 6 inhibition rescues axonal transport impairments and prevents the neurotoxicity of HIV-1 envelope protein gp120

Abstract: Despite successful antiretroviral drug therapy, a subset of human immunodeficiency virus-1 (HIV)-positive individuals still display synaptodendritic simplifications and functional cognitive impairments referred to as HIV-associated neurocognitive disorders (HANDs). The neurological damage observed in HAND subjects can be experimentally reproduced by the HIV envelope protein gp120. However, the complete mechanism of gp120-mediated neurotoxicity is not entirely understood. Gp120 binds to neuronal microtubules an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…One way to alter microtubule acetylation is to affect HDAC6. The envelope protein gp120 of human immunodeficiency virus 1 (HIV-1) increased the level of HDAC6 in primary rat neurons [53], while influenza A virus reduced the level of HDAC6 in infected cells [54]. We showed that MPyV infection does not affect the mRNA levels of either HDAC6 or αTAT1.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…One way to alter microtubule acetylation is to affect HDAC6. The envelope protein gp120 of human immunodeficiency virus 1 (HIV-1) increased the level of HDAC6 in primary rat neurons [53], while influenza A virus reduced the level of HDAC6 in infected cells [54]. We showed that MPyV infection does not affect the mRNA levels of either HDAC6 or αTAT1.…”
Section: Discussionmentioning
confidence: 89%
“…The stabilization of microtubules and their acetylation favors motor binding, thus enhancing their movement along the microtubules [53,61]. The disruption of microtubules by nocodazole inhibited the release of MPyV from infected cells [50], suggesting that intact and likely stable microtubules are indispensable for the active release of MPyV progeny from infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Synaptopathy has emerged as a hallmark of HIV-mediated neurotoxicity of HAND in the post-cART era [74] and impairments in neuronal cytoskeleton are highly relevant driven by neurotoxic HIV proteins [93][94][95]. Synaptic dysfunction and dendritic simplification are linked to gp120 neurotoxicity and underlie cognitive impairments observed in HAND yet the mechanisms are poorly understood [12,96,97].…”
Section: Plos Onementioning
confidence: 99%
“…An area of great interest is the treatment of human immunodeficiency virus (HIV)-associated neurocognitive disorders. The neurological damage observed in HIV-positive subjects can be experimentally reproduced by the HIV envelope glycoprotein (gp)120. gp120 binds to neuronal microtubules and decreases the level of tubulin acetylation, with resulting impairment of axonal transport [ 54 , 55 ]. Wenzel et al [ 54 ] showed that the selective HDAC6i tubacin and ACY-1215 prevented gp120-mediated deacetylation of tubulin and inhibited the ability of gp120 to decrease axonal transport.…”
Section: Cognition Regulation and Neurodegenerationmentioning
confidence: 99%
“…The neurological damage observed in HIV-positive subjects can be experimentally reproduced by the HIV envelope glycoprotein (gp)120. gp120 binds to neuronal microtubules and decreases the level of tubulin acetylation, with resulting impairment of axonal transport [ 54 , 55 ]. Wenzel et al [ 54 ] showed that the selective HDAC6i tubacin and ACY-1215 prevented gp120-mediated deacetylation of tubulin and inhibited the ability of gp120 to decrease axonal transport. Indeed, the study showed that gp120 decreases the velocity of BDNF transport, which is restored to baseline levels when neurons are exposed to HDAC6i [ 55 ].…”
Section: Cognition Regulation and Neurodegenerationmentioning
confidence: 99%